OBJECT MODELS WITH VECTOR STEERING - Hauge R.; Syversveen A.R.; Macdonald A. (My University, 2006)
Object models are widely used to model the distribution of facies in a reservoir. Several computer programs exist for modelling fluvial channels or more general facies objects. This paper focuses on a marked point model with objects that are able to orient locally according to a vector field. In this way, objects with locally varying curvature are created. With this kind of objects it is possible to model complex depositional basins, that are not easily modelled with conventional methods. The new object type is called Backbone objects. The objects have a piecewise linear centerline and are able to follow the direction of a three-dimensional vector field locally in lateral and vertical direction. How well the objects follow the vector field is determined by three parameters. Use of different coordinate systems and mapping between the systems make it possible to generate Gaussian random fields that follow the shape and direction of the objects. The Gaussian fields can be used to model petrophysical variables, which is important for fluid flow modelling.
Keywords: FACIES MODELLING; VECTOR FIELD; BACKBONE OBJECTS; LOCAL ORIENTATION; TURBIDITES